The Predictive Value of Pathologic Features in Pituitary Adenoma and Correlation with Pituitary Adenoma Recurrence - Jee Soon Kim; Youn Soo Lee; Min Jung Jung; Yong Kil Hong (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Background The 2004 World Health Organization classification introduced atypical pituitary adenoma (aPA), which was equivocally defined as invasion with increased mitotic activity that had a Ki-67 labeling index (LI) greater than 3%, and extensive p53 immunoreactivity. However, aPAs that exhibit all of these features are rare and the predictive value for recurrence in pituitary adenomas (PAs) remains uncertain. Thus, we sought to characterize pathological features of PAs that correlated with recurrence. Methods One hundred and sixty-seven cases of surgically resected PA or aPA were retrieved from 2011 to 2013 in Seoul St. Mary's Hospital. Among them, 28 cases were confirmed to be recurrent, based on pathologic or radiologic examination. The pathologic characteristics including mitosis, invasion, Ki-67 LI and p53 immunoreactivity were analyzed in relation to recurrence. Results Analysis of the pathologic features indicated that only Ki-67 LI over 3% was significantly associated with tumor recurrence (p = .02). The cases with at least one pathologic feature showed significantly higher recurrence rates (p < .01). Analysis indicated that cases with two pathologic features, Ki-67 LI over 3% and extensive p53 immunoreactivity 20% or more, were significantly associated with tumor recurrence (p < .01). Conclusions Based on these results, PA tumor recurrence can be predicted by using mitosis, invasion, Ki-67 LI (3%), or extensive p53 immunoreactivity (≥ 20%). Assessment of these features is recommended for PA diagnosis for more accurate prediction of recurrence.